Pengaruh Profitability, Non-Debt Tax Shield, Growth Opportunity, Corporate Tax Rate Terhadap Capital Structure Pada Perusahaan Manufaktur Yang Terindeks BEI Periode 2018-2022 - Andhika Perkasa F; Suwito; Sardju, Fitriani (Insan Cita Bongaya Research Journal, 2023)
This study aims to examine the effect of profitability, non-debt tax shield, growth opportunity, coprporate tax rate on capital structure. The population in this study are manufacturing companies listed on the Indonesian Stock Exchange (BEI). With 115 samples selected using purposive sampling techniques.This study uses multiple linear regression models. The results of the study indicate that Profitability has no effect on Capital Structure. Non-Debt Tax Shield has no effect on Capital Structure. Growth Opportunities have a positive effect on Capital Structure. Corporate Tax Rate has no effect on Capital Structure